Katie Brooks: capstone - Brooks, Katie, artist (Colorado State University. Libraries, 2018)
The artist's statement: Like many other designers, my interest in design began at a young age when I became infatuated with drawing horses. This involved using the application Paint on my 2003 DELL, and subsequently trying to sell the drawing to my friends on the playground at school. Now, as a soon-to-be college graduate with a focus in graphic design, I can safely say that my skills have surpassed Paint. My college education has provided me with a diverse array of technical design skills that I have been fortunate enough to put into practice during my internship at the Career Center. I aspire to design high-quality print, web, and social graphics, utilizing a variety of Adobe Creative Cloud applications. My work at the Career Center has been predominantly client-based. Having worked with 20+ clients, I have become accustomed to working collaboratively, often applying feedback to exceed client expectations. Given the fast-paced nature of the Career Center, I have become efficient in handling projects concurrently, whilst maintaining a keen eye for detail and deadlines. Though I have learned a great deal during my college career, one thing I have always known - even when I worked on drawing horses in paint - is that I have a passion for design and marketing.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design